Sharia Economic Transformation: Adaptation of Sharia Law to Global Market Dynamics - Bachrul Ulum (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The transformation of the sharia economy through the adaptation of sharia law to global market dynamics represents a significant phenomenon in contemporary economic development. In the current era of globalization, Islamic economics has emerged as a driving force that influences the structure and direction of the global financial system. The main issue addressed in this study is how sharia principles can remain consistent while responding effectively to rapid global market changes. The objective of this research is to explain the process of sharia economic transformation and examine the extent to which the adaptation of sharia law can strengthen financial inclusion, enhance economic stability, and promote sustainable economic growth. This study employs a literature review method, drawing on books and scholarly sources relevant to Islamic economics, global market behavior, and the governance of sharia law. The findings indicate that the transformation of the sharia economy—supported by the adaptation of its legal framework—has led to increased financial inclusion, broader market expansion, and stronger economic resilience. Moreover, the integration of Islamic finance within global markets has contributed to economic stability and fostered a more ethical and socially responsible business environment. The study concludes that transforming the sharia economy through adaptive legal approaches is a crucial step toward achieving inclusive finance, sustainable stability, and social justice. This process enhances the relevance, competitiveness, and long-term viability of the sharia economic system in an evolving global market landscape.